2016
DOI: 10.1016/j.ajoc.2016.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Ophthalmic considerations in patients with Pfeiffer syndrome

Abstract: PurposeWe report here a newborn male infant with striking features consistent with severe Pfeiffer syndrome type II, including cloverleaf skull deformity with pansynostosis, extreme proptosis, upper extremity contractures, broad big toes and thumbs with varus deviation and genetic mutation in the FGFR2 gene. The authors review the ophthalmic complications in Pfeiffer syndrome and discuss the unique surgical strategies used for obtaining adequate corneal coverage in these unique patients.ObservationsOphthalmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
1
6
0
4
Order By: Relevance
“…Pfeiffer syndrome has also been associated with other systemic anomalies like tracheobronchial tree anomalies, congenital heart defects, renal, aqueduct stenosis, hydrocephalus, cerebellar and brain stem herniation, low‐set ears, external auditory canal stenosis or atresia and, unusually, hydronephrosis, pelvic kidney and hypoplastic gallbladder, micro phallus, cryptorchidism, growth and mental retardation 4,5,7 We also found cranial, cardiac, and renal involvement in our patient associated with this syndrome.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Pfeiffer syndrome has also been associated with other systemic anomalies like tracheobronchial tree anomalies, congenital heart defects, renal, aqueduct stenosis, hydrocephalus, cerebellar and brain stem herniation, low‐set ears, external auditory canal stenosis or atresia and, unusually, hydronephrosis, pelvic kidney and hypoplastic gallbladder, micro phallus, cryptorchidism, growth and mental retardation 4,5,7 We also found cranial, cardiac, and renal involvement in our patient associated with this syndrome.…”
Section: Discussionsupporting
confidence: 63%
“…Our patient had clinical findings consistent with Pfeiffer syndrome (PS) type 2, which consists of cloverleaf skull deformity due to extensive craniosynostosis, agenesis of corpus callosum, hand and foot anomalies like elbow synostosis, brachydactyly, and varus deformities of the toes, with additional bilateral choanal atresia, cardiac and renal anomalies. PS type 2 has been reported with similar presentation in many literatures from the Western world 7,9,10 . However, Badoe et al 8 reported two cases of Pfeiffer syndrome subtype 3 from west Africa over a 10‐year period indicating the rarity of this syndrome in African population.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations